Clostridium difficile: Investigating Transmission Patterns Between Infected and Colonized Patients Using Whole Genome Sequencing. (28th May 2018) - Kong, Ling Yuan; Eyre, David W; Corbeil, Jacques; Raymond, Frederic; Walker, A Sarah; Wilcox, Mark H; Crook, Derrick W; Michaud, Sophie; Toye, Baldwin; Frost, Eric; Dendukuri, Nandini; Schiller, Ian; et al.
Abstract : Using whole genome sequencing of isolates from a cohort of patients with Clostridium difficile infection (CDI) and colonization, we found that incident CDI cases were more likely to be linked to an infected than colonized donor. Abstract: Background: Whole genome sequencing (WGS) studies can enhance our understanding of the role of patients with asymptomatic Clostridium difficile colonization in transmission. Methods: Isolates obtained from patients with Clostridium difficile infection (CDI) and colonization identified in a study conducted during 2006–2007 at 6 Canadian hospitals underwent typing by pulsed-field gel electrophoresis, multilocus sequence typing, and WGS. Isolates from incident CDI cases not in the initial study were also sequenced where possible. Ward movement and typing data were combined to identify plausible donors for each CDI case, as defined by shared time and space within predefined limits. Proportions of plausible donors for CDI cases that were colonized, infected, or both were examined. Results: Five hundred fifty-four isolates were sequenced successfully, 353 from colonized patients and 201 from CDI cases. The NAP1/027/ST1 strain was the most common strain, found in 124 (62%) of infected and 92 (26%) of colonized patients. A donor with a plausible ward link was found for 81 CDI cases (40%) using WGS with a threshold of ≤2 single nucleotide polymorphisms to determine relatedness. Sixty-five (32%) CDI cases could be linked to both infected and colonized donors. Exclusive linkages to infected and colonized donors were found for 28 (14%) and 12 (6%) CDI cases, respectively. Conclusions: Colonized patients contribute to transmission, but CDI cases are more likely linked to other infected patients than colonized patients in this cohort with high rates of the NAP1/027/ST1 strain, highlighting the importance of local prevalence of virulent strains in determining transmission dynamics.